Cooperative Resilience of Cyber–Physical Power Systems Under Hybrid Attacks via Dynamic Topology - Jin, Jiahui; Liu, Yonghui; Li , Peiyue; Chang , Mengyan (Frontiers in Energy Research, 2022)
In this study, the cooperative resilience of cyber–physical power systems under hybrid attacks is investigated. First, a detection model of physical attacks depending on the residual of the output impedance angle is established. Second, by analyzing the encrypted communication between physical and cyber systems, a detection algorithm for cyberattacks is proposed. Then, by using an enumeration method, islanded cyber–physical power systems are built with non-attacked and repaired parts. Moreover, to save resilient resources, cooperative optimization is established after the individual optimization of islanded cyber and physical systems. Since the building and optimization are executed alternately, the topology of the systems is dynamic. Finally, simulation results demonstrate the effectiveness of the proposed method.